How to hike like a pro - Norris, Ashley P. Watson (Outdoor sports skills., 2015)
"In this 'How-to' guide, learn the basic skills of hiking including how to pick a route, how to pack and dress appropriately, and what might be encountered while on a hike"--Publisher.